IDENTITĂŢI LITERARE – 2011 (I) - RUSU, Nicolae (BIBLIOPOLIS, 2020)
This is a ctitical presentation of the recent succsesfull work of the Roumanian writers from Chişinău thrpough the prism of demands of the Jury of the Moldova Writers Union. The author analyse carefull the literary production of the 2011, by categories which coincide with the literary genres: children books, prose, poetry, essays, memoirs etc. Thus the librarians and readers have at hand a guide of authors worth reading.